2018
DOI: 10.1007/s00792-018-1024-9
|View full text |Cite
|
Sign up to set email alerts
|

Acidithiobacillus ferrooxidans and its potential application

Abstract: The widely distributed Acidithiobacillus ferrooxidans (A. ferrooxidans) lives in extremely acidic conditions by fixing CO and nitrogen, and by obtaining energy from Fe oxidation with either downhill or uphill electron transfer pathway and from reduced sulfur oxidation. A. ferrooxidans exists as different genomovars and its genome size is 2.89-4.18 Mb. The chemotactic movement of A. ferrooxidans is regulated by quorum sensing. A. ferrooxidans shows weak magnetotaxis due to formation of 15-70 nm magnetite magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 136 publications
0
60
0
1
Order By: Relevance
“…[ 39–42 ] These bacteria have been observed in a wide range of ecosystems, ranging from marine sediments, lagoons, ponds, soils to some extreme environments. [ 43–47 ] Other nonbacterial prokaryotes such as sulfur‐reducing, hyperthermophilic, heterotrophic archaea can also produce greigite. [ 48 ] The earliest reports of magnetotactic bacteria (MTB) in 1963 [ 49 ] and 1975 [ 50 ] pioneer the discovery of MTB with diverse morphology, including cocci, spirilla, vibrios, ovoid bacteria, rod‐shaped bacteria, and multicellular bacteria.…”
Section: Microbe‐mediated Mineralization In Naturementioning
confidence: 99%
“…[ 39–42 ] These bacteria have been observed in a wide range of ecosystems, ranging from marine sediments, lagoons, ponds, soils to some extreme environments. [ 43–47 ] Other nonbacterial prokaryotes such as sulfur‐reducing, hyperthermophilic, heterotrophic archaea can also produce greigite. [ 48 ] The earliest reports of magnetotactic bacteria (MTB) in 1963 [ 49 ] and 1975 [ 50 ] pioneer the discovery of MTB with diverse morphology, including cocci, spirilla, vibrios, ovoid bacteria, rod‐shaped bacteria, and multicellular bacteria.…”
Section: Microbe‐mediated Mineralization In Naturementioning
confidence: 99%
“…Based on the COG analysis (Table 2), the functional genes related to defense mechanisms (V), cell wall/membrane/envelope biogenesis (M), amino acid transport and metabolism (E), inorganic ion transport and metabolism (P) and general function prediction only (R) were slightly more than the other genes. These revealed that this strain exhibited excellent environmental adaptability and has potential applications in ecological industry such as sulfur removal from gases, mental extraction from electronic waste [44]. Additionally, the genes associated with function unknown (S) indicated that strain YNTRS-40 might possess some new genes [45].…”
Section: Genomic Features Related To Adaptation To Diverse Stressesmentioning
confidence: 99%
“…Based on the COG analysis (Table 2), the functional genes related to defense mechanisms (V), cell wall/membrane/envelope biogenesis (M), amino acid transport and metabolism (E), inorganic ion transport and metabolism (P) and general function prediction only (R) were slightly more than the other genes. These revealed that this strain exhibited excellent environmental adaptability and has potential applications in the ecological industry, such as sulfur removal from gases, metal extraction from electronic waste [21]. Additionally, the genes associated with function unknown (S) indicated that strain YNTRS-40 might possess some new genes [50].…”
Section: Genomic Features Related To Adaptation To Diverse Stressesmentioning
confidence: 99%
“…ferrooxidans has iron-and sulfur-oxidizing abilities and can grow in the environments with high concentrations of metal ions such as pyritic ore bodies, coal deposits and their acidified drainages [15][16][17][18][19][20]. Therefore, it has potential utilization in microbial electrosynthesis systems, eco-friendly bioleaching technology, biological desulfurization and machining of workpieces [21]. Until now, nine A. ferrooxidans strain genomes (ATCC 23270, ATCC 53993, Hel18, BY0502, CCM 4253, IO-2C, YQH-1, DLC-5, and RVS1) have been available in the public databases.…”
Section: Introductionmentioning
confidence: 99%